Advanced PCR-based molecular diagnosis of gastrointestinal infections: challenges and opportunities. (2nd June 2016) - Zboromyrska, Yuliya; Vila, Jordi
ABSTRACT: Acute infections of the gastrointestinal tract are among the most common infectious diseases. The etiological agents of gastroenteritis may be bacteria, viruses or protozoa. Identification of the etiological agents of acute diarrhea is important for the treatment and management of diarrheal diseases. Conventional stool culture for bacteria shows a low sensitivity and requires more than 24 hours. In addition, other approaches to detect viruses and protozoa mainly involve antigen detection, but this is not available for all enteropathogens, and microscopic observation requires training and is of low sensitivity. In this review, the authors describe currently available molecular methods to detect different enteropathogens and analyze the main advantages and disadvantages of these methods for laboratory diagnosis of gastroenteritis.